PLACE OF LINGUO-DIDACTIC ONLINE PLATFORM IN THE SYSTEM OF TEACHING RUSSIAN AS A FOREIGN LANGUAGE: SEARCH FOR NEW TECHNOLOGIES - Petrova, Svetlana (Revista Inclusiones, 2020)
The relevance of the issue under investigation is determined by the need to develop an innovative method for teaching the Russian language to foreigners and to introduce materials into the linguodidactic online platform “Russian studies in the North-East of Russia and in countries of the Pacific Rim”. The method is based on the graphical and symbolic analysis of a work of fiction within the system of teaching Russian to foreigners. This system will be the most consistent with the state’s strategy to promote the Russian language abroad. This is all the more relevant considering that over 400 foreigners from the Pacific Rim, Africa, Middle East, Europe and Latin America are studying at the M.K. Ammosov North-Eastern Federal University.